Zakat Impact on Poverty and Welfare of Mustahik: A CIBEST Model Approach - Irfan Syauqi Beik; Caesar Pratama (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
This research aims to analyze the impact of productive zakat program in poverty alleviation of mustahik households, based on materially and spiritually aspects. Primary data was used as the source of data through distributing administered questionnaires in four rural areas in Bogor Regency. 121 respondents had been interviewed. They were the recipients of Masyarakat Mandiri program of Dompet Dhuafa Amil Institution. CIBEST model which have been developed by Beik dan Arsyianti (2014) was used as the tool of analysis. CIBEST model comprising four indices is used as tool of analysis. These indices are welfare index, material poverty index, spiritual poverty index and absolute poverty index. It is found that the presence of zakat utilization program is able to increase welfare index of the mustahik by 147.14 percent. The material poverty index, spiritual poverty index and absolute poverty index can also be reduced by 49.6 percent 1.6 and 12.3 percent, respectively. Meanwhile, welfare index increase by 63.7 percent. In conclusion, productive zakat program give positive impact to the mustahik household life.Keywords: CIBEST model, Islamic poverty index, poverty, productive-based zakat program